Pelatihan Mental Sehat Untuk Pengembangan Resiliensi Guru - Gian Sugiana Sugara; Anandha Putri Rahimsyah; Muhammad Muhajirin (Kreativasi : Journal of Community Empowerment, 2024)
Teachers have a responsibility not only to deliver lesson material, but also to shape the character and mental well-being of students. For this reason, the Guidance and Counseling Study Program at the Muhammadiyah University of Tasikmalaya held a "Healthy Mental Training" program at the Nurul Amal Ciamis Islamic Boarding School, discussing healthy mental management and a healthy mental mindset. This training aims to provide an in-depth understanding of mental health, provide knowledge about mental health disorders, symptoms, and how to manage them, and educate teachers about the importance of supporting students who experience mental health problems. The activity method involves preparation, implementation and evaluation, with a focus on teachers' understanding and awareness of the importance of students' mental health. The article highlights efforts to empower teachers as agents of change in creating an educational environment that supports growth for both teachers and students.